Perceived personal impact and trust in management as a determinants for resistance to change - Mat, Norazuwa; Romli, Ruslan (2013)
This study examines the determinants to resistance to change in a business organization.Two factors namely Perceived Personal Impact and Trust in Management were selected to test the possibility of having a simple but comprehensive model that can predict resistance to change.A survey questionnaire was chosen as the instrument of choice to collect the data for this study. Collected data was entered into SPSS 12.0 for statistical analysis.The data was then analyzed using Pearson Correlation Analysis and Multiple Regression Analysis to test the hypotheses. The two factors were found to have a relationship with resistance to change.The findings from this research helps to explain how change resistance antecedents relates to one another and the circumstances that it can become the underlying factor that results in resistance to change at workplace.